2002
DOI: 10.1172/jci0215219
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3 is a negative endocrine regulator of the renin-angiotensin system

Abstract: IntroductionThe renin-angiotensin system is a regulatory cascade that plays an essential role in the regulation of blood pressure, electrolyte, and volume homeostasis. The first and rate-limiting component of this cascade is renin, a protease synthesized and secreted predominantly by the juxtaglomerular (JG) apparatus in the nephron. Renin cleaves angiotensin I (Ang I) from liver-derived angiotensinogen, which is then converted to Ang II by the angiotensin-converting enzyme. Ang II, through binding to its rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
641
5
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,538 publications
(707 citation statements)
references
References 40 publications
19
641
5
7
Order By: Relevance
“…In addition, Al Mheid et al [22] reported that 25(OH)D insuffi ciency was associated with increased arterial stiff ness and endothelial dysfunction in a community-based asymptomatic population. Another mechanism may be pancreatic β-cell dysfunction, peripheral tissue resistance to insulin predisposing to diabetes [23], and activation of the renin-angiotensin system predisposing to hypertension [24]. In addition, Oh et al [25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Al Mheid et al [22] reported that 25(OH)D insuffi ciency was associated with increased arterial stiff ness and endothelial dysfunction in a community-based asymptomatic population. Another mechanism may be pancreatic β-cell dysfunction, peripheral tissue resistance to insulin predisposing to diabetes [23], and activation of the renin-angiotensin system predisposing to hypertension [24]. In addition, Oh et al [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact reasons for these diverse results are unclear, they may be attributed to differing ARBs, methods of measuring AngII levels, and the renal disease models used. In addition, vitamin D decreases renin expression [3]. Accordingly, plasma renin activity and AngII levels reduced in the V group.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic cardiovascular complications are very common among patients with CKDs, and suppression of the RAS retards the progression of renal dysfunction in various CKDs [1]. Recent findings indicate that vitamin D diminishes renin expression [3]. Thus, vitamin D may exert renoprotective effects through the inhibition of the RAS.…”
Section: Introductionmentioning
confidence: 99%
“…Выявлено, что по-сле использования 2 доз препарата экспрессия ренина снизилась на 35%, а после назначения 5 доз -на 50%. Кроме того, на культурах клеток экспериментально уста-новлено, что кальцитриол непосредственно подавляет транскрипцию гена ренина по VDR-зависимому меха-низму [52]. Таким образом, в этом исследовании авто-ры предоставили данные как in vivo, так и in vitro о том, что витамин D действительно является потенциально не-гативным регулятором РАС.…”
Section: витамин D и функция β-клеток поджелудочной железыunclassified